NUTRITION OF LUMUT BANANA (Musa Acuminate Colla) AMBON PEEL AT SEVERAL LEVEL OF FRUIT MATURITY - Maitimu, Musa; Wakano, Delly; Sahertian, Dece (Universitas Pattimura, 2020)
Banana peel is a waste from processed ripe bananas such as making various types of cakes from banana flesh, while unripe banana peels are waste from unripe bananas whose flesh is made into chips and contains a lot of latex when compared to ripe and overripe banana peels. This may affect the nutritional content in the two banana peels, because the maturity level of the banana peel affects the nutrient content in the peel. Based on this, this research needs to be carried out with the aim of knowing the nutritional content of raw, ripe and overripe Ambon Moss banana peels (Musa accuminata colla) in Ambon City, Maluku Province. The method used in this study is descriptive quantitative, namely to determine the analysis of the nutritional value of carbohydrates, protein, fat, and calcium in raw and ripe Ambon Moss Banana (Musa accuminata colla) peels in Ambon City, Maluku Province. The results that have been obtained are that the raw Ambon banana peel has an average carbohydrate content of 4.02%, a fat content of 0.85% and a protein content of 0.31%. Ripe Ambon banana skin has an average carbohydrate content of 4.11%, fat content of 1.19% and protein content of 0.31%. Meanwhile, in the overripe Ambon banana peel, the average carbohydrate content was 3.96%, the fat content was 1.68% and the protein content was 0.64%.